Analysis of determinants of value added tax revenue in Asia - Daniel Gusta Permadi; Suparna Wijaya (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study aims to obtain empirical evidence of factors that influence VAT receipts from various aspects, including the VAT rate itself, economic factors, tax administration factors, and legal factors. The VAT rate factor is explained by the standard rate and implicit rate variables. Economic factors are explained by the variables of imports, the service sector, and the fiscal deficit. Administrative factors are explained by the variable c-efficiency and government effectiveness. The legal factor is explained by the variables of controlling corruption and law enforcement. This study uses secondary data with the object of research being countries in the Asian continent from 2015 to 2019. The sample countries were selected with certain considerations so that 19 sample countries were obtained. The results of this study indicate that implicit tariffs, the service sector, and government effectiveness have a significant positive effect on VAT receipts, while imports have a significant negative effect on VAT receipts. Meanwhile, standard rates, fiscal deficits, c-efficiency, corruption control, and the rule of law have no significant effect on VAT revenues.